"We don't know who be who": post-party politics, forum shopping and Liberia's 2017 elections. Issue 5 (3rd July 2020) - Pailey, Robtel Neajai; Harris, David
ABSTRACT: Liberia's 2017 elections represented a watershed moment in the country's political history. In addition to completing the first democratic transfer of power from one president to another since 1944, it resulted in wide representation across many different parties and independents as well as high levels of legislative turn-overs. Additionally, these polls brought forward unprecedented numbers of party reconfigurations, increased levels of defections, and politicians/parties losing abysmally in presumed ethno-regional bases. In this article, we argue that Liberia currently exists in a post-war arena of "post-party" politics where a profound disregard for parties is the norm, and in which the electorate and politicians alike forum shop for candidates and/or political configurations they presume will deliver the best results at national, sub-national and local levels. Although literature exploring electoral trends in Africa tends to over-emphasize ethno-regionalism as a driver and constraint in the choices of voters and politicians, we demonstrate instead that Liberians make relatively informed, strategic decisions about political alliances and ballot casting thereby subverting allegiances to ethnicity and region. By further eschewing party loyalties, Liberians have gradually become astute forum shoppers in a political marketplace that makes running for office and voting complex undertakings.